The role of wave-particle interactions in cold and warm plasma heating - Usanova, M. E.; Delzanno, G. L.; Maruyama, N. (Frontiers in Astronomy and Space Sciences, 2025)
Cold plasma originating from the ionosphere is a highly influential component of the magnetosphere, dominating its mass. It is typically treated as a passive background represented as an empirical density in models of the ring current, outer radiation belt, and wave propagation. While it is well established that cold plasma density plays a critical role in controlling wave properties - such as amplitude and wave vector - increasing theoretical and observational evidence suggests that cold plasma populations may actively couple with waves, exchanging energy through processes that are not yet fully understood. Importantly, these processes can energize cold plasma, gradually transforming it into warm and eventually hot plasma. This mini-review explores the role of wave-particle interactions in cold and warm plasma heating, highlighting their significance in facilitating coupling between different plasma populations in Earth’s magnetosphere.